The effect of diluent gases on the growth of β-SiC films by laser CVD with HMDS. (December 2015) - Zhu, P. P.; Tu, R.; Zhang, S.; Han, M. X.; Xu, Q. F.; Sun, Q. Y.; Zhang, L. M.; Goto, T.; Yan, J. S.; Li, S. S.
Abstract : β -SiC films have been fabricated on (100) Si substrates by laser chemical vapour deposition using hexamethyldisilane ( (CH3 )3 -Si-Si-(CH3 )3 ) as a source precursor while argon or hydrogen as a diluent gas, respectively. The effects of different diluent gases species on the microstructure and deposition rate have been investigated by varying the flow rate of hexamethyldisilane ( f HMDS ). The results showed that pyramid, flower and needle-like morphologies were obtained using argon as diluent gas, whereas only pyramid with little flower structure appeared in the case of hydrogen. The deposition rate ( R dep ) was in proportion to the f HMDS irrespective of diluent gases. R dep was nearly 50% higher for hydrogen as diluent gas.